Active Ingredients and Action Mechanisms of Yi Guan Jian Decoction in Chronic Hepatitis B Patients with Liver Fibrosis. (3rd September 2019) - Li, Guangyao; Zhou, Yuan; Sze, Daniel Man-Yuen; Liu, Chao; Zhang, Qianru; Wang, Zihao; Yu, Hua; Chan, Ging; Wu, Zhongdao; Su, Shibing; Hu, Yuanjia
Abstract : Background and Aim . The progression of liver fibrosis in chronic hepatitis B (CHB) patients is currently insufficiently controlled worldwide. The Yi Guan Jian decoction (YGJD) has been widely used in the treatment of liver fibrosis in CHB cases. Although animal studies have reported the antifibrotic effects of the decoction, the active ingredients of the YGJD remain unknown. This study aimed at identifying the potential active ingredients and exploring the mechanisms of action (MOA) of the decoction when treating CHB patients with fibrosis. Methods . Using data mining techniques and a structural clustering analysis, the potential active ingredients were determined. A network analysis of the differentially expressed genes was conducted to identify the potential targets. Selected compounds were docked to the potential targets for the compound-target interaction simulation. In vitro validation, including a cell proliferation assay and Western blot analysis, was conducted to evaluate the prediction results. Results . In the microarray data, 224 differentially expressed genes related to liver fibrosis were considered to be potential targets. Thirty active ingredients of the YGJD and 15 main targets and relevant pathways were identified. Among them, two active ingredients, methylophiopogonone A and 8-geranyloxypsoralen, were validated as exhibiting antifibrotic effects on hepatic stellate cells. Conclusions . We identified the potential active ingredients of the YGJD and proposed the possible explanation for the MOA in the treatment of CHB patients with liver fibrosis. Moreover, this study provides a methodological reference for the systematic investigation of the bioactive compounds and related MOA of a traditional Chinese medicine formula in a clinical context.